Análise da acessibilidade das estações de transporte público por BRT na cidade do Rio de Janeiro após os Jogos Olímpicos de 2016 - Rodrigues, Thiago Teiji Sato Velasco (Universidade Federal de São Carlos, 2023)
The cities chosen to host Olympic Games go through various adaptation processes in a short period in order to execute the event properly. The development of local urban mobility is included in these processes and its realization directly impacts the population of the region. In this way, this study analyzes the impact on accessibility to the high-capacity public transport system in the city of Rio de Janeiro, with a focus on the BRT system, as a result of the Olympic mega-event, which took place in 2016, as well as its effects on society. To this end, socio-spatial analyses were carried out on the efficiency of the service coverage of the city's BRT stations using the QGIS program, comparing the coverage areas of each access point to the BRT system with the demographic density of each neighborhood in the municipality. After carrying out the analyses, it was possible to conclude that the BRT stations, with the completion of the Transbrasil corridor, have the potential to serve around 15% of Rio de Janeiro's urban area and 9% of the local population. These figures alone are insufficient to measure the quality of the city's public transport system, and analysis based on other indicators is necessary, but it is possible to see the potential for regional development and the benefits to the population generated by the evolution of public transport infrastructure after the Olympic mega-event in 2016.
Analysis of the accessibility of public transport stations by BRT in the city of Rio de Janeiro after the 2016 Olympic Games
Keywords: Transporte coletivo urbano; BRT; Mobilidade urbana; Sistemas de transporte; Olimpíadas; Megaeventos; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES